Multiple Punishments for the Same Offense: The Analysis After Missouri v. Hunter or Don Quixote, the Sargasso Sea, and the Gordian Knot - George C. Thomas III (Washington University Law Quarterly, 1984)
This Article will trace the development of the multiple punishment doctrine. It will examine the doctrine as it existed prior to Sours v. State, the conflict engendered by Sours, and three important Supreme Court multiple punishment cases decided after Sours. Although some areas of uncertainty remain, it is this author's position that the multiple punishment doctrine now has a coherent theoretical basis.
Keywords: Compound offenses; Double jeopardy; Punishment in crime deterrence; Sentences (Criminal procedure); United States